ASAS KEBEBASAN BERKONTRAK DALAM PERJANJIAN DISTRIBUTOR DAN PENGARUHNYA TERHADAP PRAKTEK PERSAINGAN USAHA TIDAK SEHAT - Sii, Nelson; William Pantow, Aaron; P.A. S. Sinaga, Irene (Wacana Paramarta: Jurnal Ilmu Hukum, 2024)
The principle of general freedom of contract is a fundamental principle in contract law which gives contracting parties the freedom to determine the terms of the agreement according to their respective wishes, as long as it does not conflict with the law and the application. However, in the context of distributor agreements in Indonesia, freedom of contract can also have an impact on unfair business competition practices. This research aims to examine the principle of freedom of contract in distribution agreements and its influence on unfair business competition practices using normative legal research methods. Through this approach, research identifies the historical legal background and statutory regulations that underlie freedom of contract in distributor agreements in Indonesia. The results of the research show that freedom of contract, while being an important principle to provide space for contracting parties, can also provide a loophole for distributors to practice unfair business competition. The impact can be the formation of monopolies, oligopolies, market domination, and unfairness in competition. The authority of the Business Competition Supervisory Commission (KPPU) is important in supervising distributor agreements and tackling unhealthy practices that may arise from freedom of contract. KPPU has the authority to investigate, analyze and impose sanctions on violations of business competition law involving contract distributors.